Development of Computer Based Test Which is Integrated with Bengkulu Local Wisdom to Measure the Scientific Literacy Skills of Junior High School Students - Nauratun Nazhifah; Abidin Pasaribu; Ketang Wiyono (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
Scientific literacy is essential for students to master to solve scientific problems in society. Preparing an integrated science literacy instrument of local wisdom is an effort to measure and train these abilities so that students are ready to engage in activities related to science, technology, and the environment. The purpose of this study is to develop computer-based tests that integrate valid and practical local wisdom to measure the science literacy abilities of junior high school students. The instrument was developed using quizizz, which refers to the PISA scientific literacy framework and the local wisdom of Bengkulu. This research uses research and development methods with 4D development research models using steps to define, design, develop, and disseminate. The instrument consists of 20 multiple choice questions covering aspects of context, competence, and knowledge. The subject of this study consisted of 200 grade 7th and 8th students at a public junior high school, SMP 3 Rejang Lebong. Instruments were analyzed using expert assessment of 3 validators and classical test analysis, including item practicality and reliability. The results of the expert assessment obtained an average of 4.62 with very valid categories. An average of 3.31 with very practical criteria was obtained at the development test stage. Meanwhile, the instrument reliability distribution was 0.878, with a very high-reliability category. This shows that the integrated computer-based test of local wisdom to measure the science literacy ability of junior high school students is considered very valid and practical, and the reliability is very high.